An institutional perspective for research in waqf accounting and reporting: a case study of Terengganu state Islamic Religious Council in Malaysia - Abu Talib, Nori Yani; Abdul Latiff, Radziah; Aman, Aini (Emerald Publishing Limited, 2020)
Purpose – This paper aims to improve the understanding of the institutional pressures that shape the intention to adopt waqf accounting and reporting. The study seeks to answer two research questions as follows: what are the challenges in the adoption of waqf accounting and reporting in waqf institutions; and how do institutional pressures influence the adoption of waqf reporting in Malaysia. Drawing on the work of DiMaggio and Powell and Scott of institutional theory, this paper provides empirical evidence of institutional pressures on the adoption of waqf reporting in Malaysia and the challenges faced in adopting waqf accounting and reporting. Design/methodology/approach – This study uses qualitative research method with an explanatory case study approach. Data are collected through semi-structured interviews with the accountants of State Islamic Religious Council and Customs of Terengganu, an informal conversation with the Deputy Director of Accountant Generals Department of Malaysia and document reviews, mainly the Malaysian Accounting Standard Board Research paper. Findings – The findings show that coercive pressure such as government regulation contributes to challenges in the adoption of waqf accounting and reporting. Normative pressures contribute to challenges in formulating standardised waqf accounting and reporting, whereas mimetic pressure contributes to challenges in the comparability of the waqf accounting and reporting among the state Islamic religious councils in Malaysia. In the efforts towards the standardisation of waqf accounting and reporting practice, a similarity of the process of the standard implementation or the institutional isomorphism of the State Islamic Religious Council in Terengganu is strongly influenced from the result of the mandate of its Board members and Fatwa council members (coercive isomorphism and religion logic) and minor influence from the normative isomorphism (the result of the participants’ education and profession) as well as the result of imitating other State of Islamic Religious Councils (SIRCs) because of the ambiguity of the process or certain practice. Research limitations/implications – The study contributes to the knowledge by extending institutional theory and the possible role of religion logic in Islamic perspective to organisational behaviour and accounting development in SIRCs. This study is limited to the understanding of the challenges in the adoption of waqf accounting and reporting but could also be applicable to the adoption of other accounting standards or regulations. Practical implications – This paper offers key implications for research, in improving the understanding of contextual factors and decision to adopt waqf accounting and reporting. The standard setter needs to be aware of the influence of contextual factors that shape decision towards standardisation of accounting and reporting for waqf. Originality/value – The interplay of institutional pressures and implications of religion logic provides an interesting approach to understanding the waqf institutions’ intention to adopt accounting and reporting for waqf